A quantitative analysis of Hukou reform in Chinese cities: 2000–2016. (27th December 2018) - Zhang, Jipeng; Wang, Ru; Lu, Chong
Abstract: This paper documents the changes in China's Hukou reform before and after 2014 based on a unique data set of Hukou policy documents from Chinese cities between 2000 and 2016. We construct a Hukou registration index to measure the stringency of local Hukou qualification in Chinese cities. There are four main channels for migrants to get local urban Hukou : investment, home purchase, talent program, and employment. The requirements of the four channels have large variations across different tiers of cities between the two periods of 2000–2013 and 2014–2016. First‐tier and some second‐tier cities set high criteria for local Hukou registration that have become more stringent over time, while other cities have much lower requirements. The point account system for Hukou registration shows that cities have different preferences over workers eligible for local urban Hukou . The quantitative measures developed in this paper can be used to study a variety of topics on the social and economic consequences of labor mobility barriers.